2014
DOI: 10.5455/aim.2014.22.393-397
|View full text |Cite
|
Sign up to set email alerts
|

The Amount of Media and Information Literacy Among Isfahan University of Medical Sciences' Students Using Iranian Media and Information Literacy Questionnaire (IMILQ)

Abstract: Introduction:Media and Information literacy (MIL) enables people to interpret and make informed judgments as users of information and media, as well as to become skillful creators and producers of information and media messages in their own right. The purpose of this research was to determine the amount of Media and Information Literacy among Isfahan University of Medical Sciences’ students using Iranian Media and Information Literacy Questionnaire (IMILQ).Methods:This is an applied analytical survey research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
0
14
1
Order By: Relevance
“…Based on the results of this study, it was also known that male students' media literacy was better than female students' media literacy. The results of this study differ from several studies which state that there is no significant difference in media literacy between male and female (Ashrafi-Rizi, Khorasgani, Zarmehr, & Kazempour, 2014;Hoi et al, 2015;Ode, 2017), however, the results of this study are in line with other studies which state that women in developing countries need to get strengthening in media literacy (Sharda, 2014;Suwana & Lily, 2017). This situation certainly needs to be a concern for the ITC Education Program to increase media literacy in female groups so that they are not left behind with male groups.…”
Section: Media Literacy Of Information Technology and Computer Education Studentscontrasting
confidence: 99%
“…Based on the results of this study, it was also known that male students' media literacy was better than female students' media literacy. The results of this study differ from several studies which state that there is no significant difference in media literacy between male and female (Ashrafi-Rizi, Khorasgani, Zarmehr, & Kazempour, 2014;Hoi et al, 2015;Ode, 2017), however, the results of this study are in line with other studies which state that women in developing countries need to get strengthening in media literacy (Sharda, 2014;Suwana & Lily, 2017). This situation certainly needs to be a concern for the ITC Education Program to increase media literacy in female groups so that they are not left behind with male groups.…”
Section: Media Literacy Of Information Technology and Computer Education Studentscontrasting
confidence: 99%
“…Consistent with this study, Ashrafi-rizi et al24 used a questionnaire having 5 dimensions: (1) using media messages, (2) understanding how the media works, (3) evaluation of media messages, (4) the combination of media messages, and (5) summary of the media messages. Although these dimensions correspond to the general ML scale, it measures only one aspect of ML.…”
Section: Discussionmentioning
confidence: 89%
“…In the study by Primack et al21 on American adolescents, the last 18-item scale indicated an excellent internal consistency, with a Cronbach α of 0.87. In another study on Media Literacy Scale, acceptable reliability with a Cronbach α of 0.89 was reported 24…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast to this finding, in the study conducted by Ashrafi Rizi, the mean score of media literacy among university students was higher than moderate and relatively favorable. [ 12 ] Furthermore, results of Pounaki et al . study showed that media literacy of university students was appropriate.…”
Section: Discussionmentioning
confidence: 99%